2017
DOI: 10.1515/pjct-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of nickel (II) and zinc (II) from aqueous solutions by the biomass of yeast Yarrowia lipolytica

Abstract: This study examined the biosorption process of Ni(II) and Zn(II) from an aqueous solution by dead biomass of Yarrowia lipolytica. Optimum biosorption conditions were determined as a function of pH, biomass dosage, contact time, and temperature. The biosorbent was characterized by FTIR, which indicated the participation of hydroxyl, carboxyl, amide and amine groups in the process of binding the metal ions. The results showed that the biosorption processes of both metal ions closely followed pseudo-second order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The results indicate that within the temperature range investigated, the biological uptake of Mn(II) and Cu(II) by biomass of P. huenov was a thermal reaction; an increase in temperature resulted in accelerated ion diffusion. This was in agreement with the results of other authors, which determined that increasing temperature from 20 to 40 C resulted in an increase in the maximum biosorption of Ni(II) from 11.48 to 15.64 mg/g and of Zn(II) from 15.9 to 19.21 mg/g using Y. lipolytica biomass [67]. However, C. krusei biosorption deceased when temperature increased to 50 C, probably due to denaturation of the enzymes, reducing the uptake of copper(II) [64].…”
Section: Effect Of Temperature On Biosorptionsupporting
confidence: 93%
“…The results indicate that within the temperature range investigated, the biological uptake of Mn(II) and Cu(II) by biomass of P. huenov was a thermal reaction; an increase in temperature resulted in accelerated ion diffusion. This was in agreement with the results of other authors, which determined that increasing temperature from 20 to 40 C resulted in an increase in the maximum biosorption of Ni(II) from 11.48 to 15.64 mg/g and of Zn(II) from 15.9 to 19.21 mg/g using Y. lipolytica biomass [67]. However, C. krusei biosorption deceased when temperature increased to 50 C, probably due to denaturation of the enzymes, reducing the uptake of copper(II) [64].…”
Section: Effect Of Temperature On Biosorptionsupporting
confidence: 93%
“…The removal of such metals is an urgent issue from health, economic, and environmental points of view. Several conventional methods of heavy metals removal had been described earlier, such as ion exchange, coagulation, flotation, reverse osmosis, and electrochemical process 6 . The conventional methods were found to have many disadvantages, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Sławomir Wierzba also found that -CH 2 and CH 3 were the biosorption group in the yeast cell. 78 The peaks observed at 1650 cm À1 was attributed to amide I band (stretching vibration of C]O), 1540 cm À1 indicated the amide II band (stretching vibration of C-N and bending vibration of N-H), 1248 cm À1 was attributed to amide III band (stretching vibration of C-N and bending vibration of N-H). 79,80 Aer biosorption, the wavenumber shied to 1642 cm À1 ,1546 cm À1 ,1244 cm À1 respectively, further proved that protein played an important role in the biosorption of Cu 2+ .…”
Section: Ftir Analysismentioning
confidence: 99%